DEVELOPMENT OF A B2B MARKET PENETRATION STRATEGY FOR ANTARES EAZY CCTV PRODUCTS AT PT TELKOM INDONESIA - Zamaludin Abdulah; Putu Nina Madiawati; Arry Widodo (PT. Jurnal Center Indonesia Publisher, 2026)
The CCTV industry continues to grow rapidly and is projected to reach a global market value of USD 75 billion by 2025. Amid strong competition from international players such as Hikvision and Dahua, PT Telkom Indonesia seeks to strengthen the position of its Antares Eazy CCTV product in the B2B market. This study analyzes the determinants of Purchase Intention toward Antares Eazy using the PLS-SEM approach, focusing on Service Quality, product quality, Pricing, Trust, and Brand Awareness as a moderating variable. Data were collected from 47 companies that use or potentially use CCTV solutions. The findings demonstrate that Service Quality, product quality, and Pricing exert significant effects on Trust, which subsequently influences Purchase Intention. Brand Awareness reinforces this relationship. The findings highlight the need for improved after-sales service, product enhancement, and more competitive Pricing strategies to strengthen Antares Eazy’s competitiveness in the B2B CCTV market.